Uncertainty requirements of the European Union's Industrial Emissions Directive for monitoring sulfur dioxide emissions: Implications from a blind comparison of sulfate measurements by accredited laboratories. (2nd September 2019) - Coleman, Marc D.; Ellison, Matthew; Robinson, Rod A.; Gardiner, Tom D.; Smith, Thomas O. M.
ABSTRACT: We report results from a blind comparison of five analytical laboratories ISO/IEC 17025 (International Organization for Standardization/International Electrotechnical Commission) accredited for the analysis of sulfate collected in H2 O2(aq) from industrial stacks in accordance with the European Standard Reference Method (SRM) for sulfur dioxide (SO2 ) (EN 14791): the method produced under European Commission mandate to support the enforcement of the Industrial Emissions Directive (IED). Both "synthetic" (sodium sulfate dissolved in aqueous hydrogen peroxide [H2 O2(aq) ]) and "real" (extracted and collected from a stack simulator facility in accordance with EN 14791) samples were prepared across 2–10 and 10–290 mg·m0 −3 emission equivalent concentration ranges, respectively. From the measurements returned by the laboratories, it was found that in 35% of the former and 28% of the latter the stated expanded uncertainty limits did not intersect with the mean. It was also found with the real samples that in 30% of the 46 different concentration test levels the stated expanded uncertainty of at least two of the laboratories did not intersect. With respect to compliance monitoring, it was found that EN 14791 was capable of enforcing emission limits under the IED associated with waste incinerators (i.e., 50 mg·m0 −3 ), as only 3% of the deviations were in excess of the required uncertainty (commensurate with a 95% level of confidence). However, with respect to the use of EN 14791 for calibration of automated measuring systems (AMSs), it was found that 38.5% of the deviations were in excess of the uncertainty recommended by at least one national regulator as being necessary for EN 14791 to be an "effective tool" for the calibration of AMSs. With emission limits under the IED and the Best Available Technique Reference (BREF) documents it adopts becoming increasingly stringent, it is clear that more work is needed to determine the capability of the SRM and also alternative methods based on portable instruments. Implications : The deviations observed between laboratories ISO/IEC 17025 accredited for sulfate analysis bring into question the monitoring communities' ability to routinely meet the uncertainty requirements associated with increasingly stringent SO2 emission limits under the European Union's Industrial Emissions Directive. Furthermore, with even further reductions in the near future due to legislative adoption of BREF documents, such issues are only likely to be exacerbated. If the European monitoring community is to have confidence in the capability of the existing Standard Reference Method described in EN 14791 for enforcing increasingly stringent limits, work is needed to validate this method at these lower emission levels.